Edukasi Pemanfaatan Pekarangan Rumah Untuk Ketahanan Pangan Keluarga Di Kabupaten Bima - Mahmudah, Husnatul; Nurfarhaty; Juhriati; Rahmawati; Khairunnas; Alamsyah, Syahrul (SEWAGATI: Jurnal Pengabdian kepada Masyarakat, 2025)
One of the efforts that can be made to strengthen household food security is to use the yard as a source of independent food production. However, the use of the yard is still limited to aesthetic functions and has not been used as a source of family food. The community service program aims to increase public understanding and awareness of the importance of using the yard for food security. This activity was carried out through a socialization method for the women of the Aisyiyah Branch Leadership in three sub-districts in Bima, West Nusa Tenggara. The implementation method includes the delivery of educational materials, interactive discussions, the preparation of follow-up Actions, and participatory evaluation. The results showed that most of the participants (±85%) experienced an increase in knowledge about the concept of food security and productive use of the yard. Participants also compiled RTL as a form of commitment to apply the knowledge gained in daily life. This activity shows that community-based education has great potential to encourage changes in people's attitudes and behaviors in building independent and sustainable food security.